The Influence of Social Media Language on the Quality of EFL Students’ Academic Writing - راشد Majda Mahmoud Mohammed (مجلة الاصالة, 2026)
This study examines the impact of social media language on the quality of academic writing. Using a descriptive-analytical design, data was amassed from 50 EFL Libyan undergraduate students at Zawia University through a closed-ended questionnaire and academic essay writing tasks. The results indicate that there is a slight correlation between the preferred use of social media and academic writing ratings. However, there is a large and mildly negative correlation between the use of digital linguistic features, such as abbreviations and nonstandard grammar, and academic writing quality. This suggests that the language used in social media, rather than just its usage, is the primary factor that affects formality and grammatical accuracy. In addition, this study highlights the importance of students’ linguistic awareness and its benefits in academic contexts. Recommendations include integrating reflective practice in student writing, where assignments should encourage students to reflect on their writing choices and contrast them with social media norms, fostering self-monitoring and language control.